The Influence of Channel Integration Quality Affecting Purchasing Intention of Fast Fashion Product via Omni Channel - Sombultawee, Kedwadee; Suwannakin, Suphitsara (Business Administration and Management Journal Review, 2023)
The aim of this research is to investigate the influence of channel integration quality upon purchase intention for fast fashion products by omni channel retailing. Data was collected from 400 Thai omni channel consumers who have purchases fast fashion products. Multiple linear regression (MLR) was used. The result found that there is a significantly positive relationship exists between process consistency, service channel choice breadth, transparency of channel-service configuration, and content consistency with purchase intention for fast fashion products by omni channel retailing. In addition, these findings significantly indicate a different level of purchase intention for consumers using omni channel services, and those who do not.